Determinants, Detection, and Impacts of Fraud in Conventional Commercial Banks: A Systematic Literature Review of Scopus Q1–Q2 Articles (2019–2024) - Khairil Anwar; Pardomuan Pardosi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Fraud remains one of the most persistent and systemic risks confronting conventional commercial banks worldwide. Despite significant regulatory reforms, advancements in governance frameworks, and the adoption of sophisticated digital control systems, fraudulent activities continue to undermine bank performance, financial stability, and public trust. This study conducts a Systematic Literature Review (SLR) of more than 100 peer-reviewed articles published in Scopus-indexed Q1–Q2 journals between 2019 and 2024, focusing exclusively on conventional commercial banks. Guided by the PRISMA framework, the review synthesizes existing evidence on the determinants of bank fraud, fraud detection mechanisms, and the impacts of fraud on bank performance and stability. The findings reveal that fraud in conventional banks is primarily driven by governance weaknesses, behavioral and ethical failures, regulatory and institutional gaps, and emerging digital risks. While internal controls, auditing, forensic accounting, and advanced analytics significantly enhance fraud detection, their effectiveness varies across institutional contexts. Fraud is shown to exert substantial adverse effects on profitability, solvency, and reputational capital, with implications that extend beyond individual banks to the broader financial system. This review contributes to the literature by integrating fragmented findings into a coherent analytical framework and by identifying critical research gaps and policy implications for regulators and bank management.